Phase- and intensity-resolved measurements of above threshold ionization by few-cycle pulses - Kuebel, M.; Arbeiter, Mathias; Burger, C.; Kling, Nora G.; Pischke, T.; Moshammer, R.; Fennel, Thomas; Kling, Matthias F.; Bergues, B. (Journal of Physics B-Atomic Molecular and Optical Physics, 2018)
We investigate the carrier-envelope phase (CEP) and intensity dependence of the longitudinal momentum distribution of photoelectrons resulting from above threshold ionization of argon by few-cycle laser pulses. The intensity of the pulses with a center wavelength of 750 nm is varied in a range between 0.7 × 1014 and . Our measurements reveal a prominent maximum in the CEP-dependent asymmetry at photoelectron energies of 2 U P (U P being the ponderomotive potential), that is persistent over the entire intensity range. Further local maxima are observed around 0.3 and 0.8 U P. The experimental results are in good agreement with theoretical results obtained by solving the three-dimensional time-dependent Schrödinger equation. We show that for few-cycle pulses, the amplitude of the CEP-dependent asymmetry provides a reliable measure for the peak intensity on target. Moreover, the measured asymmetry amplitude exhibits an intensity-dependent interference structure at low photoelectron energy, which could be used to benchmark model potentials for complex atoms.
CRIS-Team Scopus Importer:2023-04-20
Keywords: above threshold ionization; carrier-envelope phase; few-cycle pulses; laser intensity; strong-field physics